Mineral analysis of complete dog and cat foods in the UK and compliance with European guidelines - Davies, M.; Alborough, R.; Jones, L.; Davis, C.; Williams, C.; Gardner, D.S. (Nature Publishing Group, 2017)
Mineral content of complete pet food is regulated to ensure health of the companion animal population. Analysis of adherence to these regulatory guidelines has not been conducted. Here, mineral composition of complete wet (n = 97) and dry (n = 80) canine and feline pet food sold in the UK was measured to assess compliance with EU guidelines. A majority of foods complied with ≥8 of 11 guidelines (99% and 83% for dry and wet food, respectively), but many failed to provide nutritional minimum (e.g. Cu, 20% of wet food) or exceeded nutritional maximum (e.g. Se, 76% of wet food). Only 6% (6/97) of wet and 38% (30/80) of dry food were fully compliant. Some foods (20–30% of all analysed) had mineral imbalance, such as not having the recommended ratio of Ca:P (between 1:1 to 2:1). Foods with high fish content had high levels of undesirable metal elements such as arsenic. This study highlights broad non-compliance of a range of popular pet foods sold in the UK with EU guidelines (94% and 61% of wet and dry foods, respectively). If fed exclusively and over an extended period, a number of these pet foods could impact the general health of companion animals.